Chariots of ladies: Francesc Eiximenis and the court culture of medieval and early modern Iberia - Silleras-Fernandez, Núria (Cornell University Press, 2015)
Introduction : Eiximenis, his patronesses, and female virtue in late medieval and early modern Iberia -- A return to piety : Eiximenis and the culture of the late medieval Catalan court (the Crown of Aragon, 1327-1409) -- Noble inspiration : Sanxa Ximenis d'Arenós and the Book of women (Valencia, c. 1380-96) -- Fit for a queen : the Scala Dei, Franciscan queenship, and Maria de Luna (Barcelona, c. 1396-1410) -- Found in translation : Isabel the Catholic reads Eiximenis (Castile, c. 1490-1516) -- Eiximenis on the Atlantic : the Chariot of ladies and Catalina of Hapsburg (Portugal, c. 1525-78) -- Conclusion : feminine virtue, female agency, and the legacy of Eiximenis